KONSEP VIDEO BASED LEARNING (VBL) DALAM MEMBANGUN SEMANGAT BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA - Chandra, Chandra Tazaka; Rahmat, Rahmat; Iswandi, Dede (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the concept of Video Based Learning (VBL) in fostering students’ learning motivation in Pancasila Education. The background of this study is based on the low level of student engagement in conventional learning, which often relies on lectures and memorization. This study uses a literature review method by analyzing relevant theories and previous research related to VBL and learning motivation. The results indicate that Video Based Learning has the potential to increase students’ enthusiasm through audiovisual presentations that combine visual and auditory elements. This approach aligns with the Cognitive Theory of Multimedia Learning, which suggests that learning becomes more effective when information is delivered through multiple channels. In the context of Pancasila Education, VBL helps present abstract values in a more concrete and contextual manner, making learning more meaningful and engaging for students. Therefore, VBL can be used as an alternative learning media to support the development of students’ learning motivation.